IDENTIFIKASI BIDANG GELINCIR PEMICU TANAH LONGSOR DENGAN METODE RESISTIVITAS 2 DIMENSI DI DESA TRANGKIL SEJAHTERA KECAMATAN GUNUNGPATI SEMARANG - Arga Brahmantyo; Tony Yulianto (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2014)
Landslides was happened by landslide surface. Landslides Identification of landslide surface using dipole-dipole array geoeletrical resistivity 2D method has been conducted at Trangkil Sejahtera Sukorejo Village Gunungpati Regency Semarang. Interpretation of subsurface structure showed in 2D. Field data has processed using RES2DINV program which gives stones resistivity distribution and depth of layers as a result. The result of RES2DINV is entered to CorelDraw to obtain 3D section. Landslide surface has detected by CorelDraw result’s. The interpretation show that at Perumahan Trangkil Sejahtera lithology consist of four layers i.e. sandstone, clay/lanau, wet clay, and topsoil. Slip surface was located on lanau/wet clay layers with resistivity 0,492-9,11 Ωm and dept of layers 2,65-6,47 m. Type landslides research area is kind of translational and rotational slides.Key words : Geoeletrical resistivity 2D, landslide surface, Trangkil Sejahtera, dipole-dipole, RESD2INV